Program Perhitungan Efisiensi Energi Radiasi Benda Hitam Melalui Metode Simpson dengan Borland Delphi 7 - Festiyed, Festiyed (Lembaga Penelitian Universitas Negeri Padang, 2008)
Has been design program to determine efesiensi radiation of black body through method Simpson applies programming language Borland Delphi. To know level of black body radiant energy is required [by] mathematical calculation of which is complicated enough and requires time sufficiently long, this thing would many generating error in calculation and data processing. Calculation program designed able to calculate efesiensi radiation of black body easily and quickly with level of a real small error that is 0219%. Key words : radiation of black body, method Simpson, Borland Delphi.